Innovating today to build a sustainable tomorrow - NG, Daryl (Institutional Knowledge at Singapore Management University, 2019)
Daryl Ng, Deputy Chairman of Hong Kong-based real estate property developer Sino Group, speaks about his ideas and ideals on the built environment, sustainability, and how business and innovation can be a force for good.